Improving Indonesia's poultry competitiveness: Exploring broiler chicken meat trade opportunities - Biyan Shandy Paramayudha; Maria Dominika Budhisatrio (Center for Indonesian Policy Studies (CIPS), 2024)
Indonesia has a promising broiler chicken meat industry with an estimated production growth of 2.3 million tonnes over 10 years. Amidst this rising production, chicken consumption among Indonesians is also increasing, although still lower than other animal protein sources like eggs and fish. The global poultry market is expected to grow considerably due to its affordability and environmental advantages. This represents a potential for Indonesia to export broiler chicken meat, one of the most consumed poultry products worldwide. This study identifies several underlying issues in Indonesia's poultry value chain that hinder food security and export opportunities. A particular problem lies in poultry inputs consisting of maize as feed and the import of Great Grandparents Stock Day Old Chick (GGPS DOC).
Keywords: 330